Challenges of Implementing E-Learning in Art History Faced by Instructors and Learners in Faculty of Art and Design, UiTM Perak - Nazrin, Nizar; Isahak Merican, Farah Merican; Abdul Samat, Syafiq (Idealogy Journal; Vol 5 No 1 (2020): Idealogy Journal (April 2020)DO - 10.24191/idealogy.v5i1.190, 2020)
Teaching method evolved from time to time and it’s not necessarily applicable to every learning condition. Scholars have made researches dividing the categories of methods and learners in order to achieve the best teaching solution. As human evolves throughout the development of technology, so do the learners perception towards learning. Conventional method of instructors being in front teaching is not relevant to current learners. In Malaysia, instructors were trained in andragogy concept which teacher-centered have been replaced with student-centered learning method. Learners are perceived as matured and well prepared in learning tertiary level education, but as the learning process began, instructors in Faculty of Art & Design, Universiti Teknologi Mara, Perak Branch found that the so- called millennial learners were not as prepared as they were expected to. Conventional learning seems did not fully utilize their capability in learning, hence adapting to their hi technology skills, a new concept of electronic learning was developed conceptually. Fully utilizing the technology of networking and online application available on learner’s mobile device, a new concept was embedded in current learning method. Triple Memory Enrichment (TriME) is an enhanced learning technique whereby online application such as Kahoot and Quizizz are used in lectures to compliment the traditional technics. It is hope with this new concept, leaners will enjoy learning more hence increasing the successful rate of learning art history.   Keywords: E-Learning, Andragogy, Kahoot, Quizzizz, Art History